Correlation of Students’ Vocabulary Mastery and Reading Comprehension at the Second grade of SMP Negeri 1 Kolaka - bimas reskiawan; hariadi syam (ELT Worldwide: Journal of English Language Teaching, 2019)
The aim of this research was to find out the correlation between the students’ vocabulary mastery and the students’ reading comprehension at the second Grade of SMPN 1Kolaka. The population of this research was all the second grade students of SMP Negeri 1 Kolaka which consist of 206 students. The sample of this research is 26 students, it is class VIII B. The instruments in this research were two kinds of test, they were vocabulary test and reading comprehension test, each test consisted of 20 multiple choice. All the data gained in this research was analyzed by using the formulation of Pearson Product Moment Correlation Coefficient. According to the result of the analysis and statistical calculate, it found that rxy was 0.705 and rt was 0.404 with the degree of freedom (df=N-nr) was 24. By comparing the values of rxy and rt, the result was rxy was bigger than rt, in other words rcount was higher than r table. It means that there was correlation between students’ vocabulary mastery and reading comprehension and coefficient correlation was high, in this case the alternative hypothesis is accepted.Based on the finding from this research, it could be concluded that vocabulary mastery helps the students to comprehend the text. To solve the problem in comprehending the text in which students should have sufficient vocabulary that can help them in doing their in reading test.